The Relationship Between Suboptimal Social Networks and Postoperative Delirium: The PNDABLE Study - Tang, Xinhui; Yv, Hui; Wang, Fei; Wang, Jiahan; Liu, Siyv; Wu, Xiaoyue; Dong, Rui; Lin, Xu; Wang, Bin; Bi, Yanlin (Frontiers in Aging Neuroscience, 2022)
Background Although it has been proven that social networks are related to cognition, studies are conducted to characterize the correlation between social networks and postoperative delirium (POD). Objective We investigated whether suboptimal social networks are a risk factor for POD, and to verify whether different levels of intimacy in the same social relationship can affect the concentration of cerebrospinal fluid (CSF) biomarkers, such as amyloid-β (Aβ42), total tau (T-tau), and phosphorylated tau (P-tau), and the mediating role of CSF biomarkers between social network and POD in middle-aged and elderly Han people. Methods Our study recruited 743 participants from The Perioperative Neurocognitive Disorder and Biomarker Lifestyle (PNDABLE) study. Confusion Assessment Method (CAM) was used to evaluate the incidence of POD and its severity was measured using the Memorial Delirium Assessment Scale (MDAS). The social networks were measured using self-reported questionnaires about social ties. Mann–Whitney U test, Logistic Regression and Independent-samples test were used for Statistical Analysis. Results The incidence of POD was 20.7%. Mann–Whitney U test showed that the total score of the social network was associated with POD (P < 0.001). Independent-samples test showed that different levels of intimacy in the same social relationship were significantly associated with CSF POD biomarkers, and mediation analyses revealed that the association between suboptimal social networks and POD was partially mediated by T-tau (proportion: 20%), P-tau (proportion: 33%), Aβ42/T-tau (proportion: 14%), and Aβ42/P-tau (proportion: 15%). Conclusion Having suboptimal social networks is a risk factor for POD in middle-aged and elderly Han people. CSF POD biomarkers can mediate the correlation between suboptimal social networks and POD, which is mainly mediated by tau protein. Clinical Trial Registration www.chictr.org.cn, identifier ChiCTR2000033439.